The association of the timing of outpatient palliative care clinic visit on the utilization of hospital services and decision making at the end of life in patients with cancer – a retrospective cohort study - Anttonen, Anu; Carpén, Timo; Nåhls, Nelli-Sofia; Kitti, Pauliina; Miinalainen, Sofia; Leskelä, Riikka-Leena; Akrén, Outi; Saarto, Tiina (BioMed Central, 2026)
Background
The timely integration of palliative care (PC) into cancer treatment improves quality of life and supports care planning at the end of life (EOL) for patients with incurable cancer. However, there is limited data on how the timing of outpatient PC clinic visits affect hospital services use and decision-making as death approaches. The study evaluated the association of outpatient PC clinic visit, and its timing, on healthcare use and decision making at the EOL in patients with cancer. Additionally, the implementation of the integrated PC was examined.
Methods
Data on all patients (n = 3744) with cancer treated at the Comprehensive Cancer Center Helsinki University Hospital during 2017–2018 and deceased by the end of 2018 were retrospectively reviewed. The data on healthcare utilization was extracted from the hospital database. The timing of the outpatient PC clinic visit was determined as follows: (1) Integrated PC visit i.e. PC was initiated alongside the usual oncological care (2) Non-integrated PC visit i.e. the first visit occurred after the termination of disease modifying treatments, and (3) No visit.
Results
In total, 2151 (57.4%) patients visited an outpatient PC clinic, and 1207 (32.2%) patients had an integrated PC visit. The median time from the first PC visit to death among integrated PC group was significantly longer compared to the non-integrated PC group (129 vs. 55 days; p < 0.001).
Patients with an integrated or a non-integrated PC visit were less likely to be hospitalized during the last 30 days of life compared to patients with no outpatient PC clinic visit (36.5% vs 43.6%; p<0.001 and 35.6% vs 43.6%; p<0.001, respectively). Patients with PC visits also had lower number of inpatient days. No significant differences were observed in emergency department visits between the groups (37.8%, 37.3% and 40.3%, respectively).
Conclusions
Overall, access to tertiary center outpatient PC clinic was relatively high, as more than half of the patients visited the outpatient PC clinic. In one third the first visit was considered as integrated. However, the first integrated visit occurred only four months prior to death. Despite this, both integrated and non-integrated outpatient PC clinic visits suggested a possible association with lower hospitalization rates and fewer inpatient days at the EOL.